Potrošnja tehnologij in tehnologije potrošnje - Petrovčič, Andraž (Javnost (Ljubljana), 2007)
This paper aims to investigate the role of new technologies in the modern consumption culture by focusing on the relation between mobile phone and contemporary consumption practices that are formed around aesthetics of temporality and hinge on the existence of a ceaseless desire for the new. The paper suggests that in the contemporary culture mobile phones are not only consumption objects, used for marking and constructing social and status distinctions, but through their perpetual presence in the everyday life are also inherently embedded in consumption practices that are oriented toward emotional, aesthetic and hedonistic experiences. Under such conditions the consumption of mobile phones is not only determined by their material qualities, related to the sense of new as fresh and/or innovative, but is primarily fostered by the purely experiential sense of new as novel or unfamiliar. With the help of a recent empirical study on social aspects of mobile telephony in Slovenia the paper explores the implications that these forms of the "newness" have on mobile phone related consumption culture. Although three different groups of mobile phone consumers were identified by cluster analysis approach, whose consumption motivations lie in three different dimensions of the new, the findings suggest that freshness, innovation, and novelty do not shape their consumption style as separated but rather as mutually interwoven categories.
Keywords: mobilni telefoni; potrošništvo; potrošniška družba; moda; fashion; družbeno vedenje; estetika; aesthetics